Efficient and transparent virtualization mechanism for volunteer computing [electronic resource] - Mohammadfazel Anjomshoa, 1987-; Mazleena Salleh; Fakulti Komputeran (2014)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2014